Preliminary study of the effects of furosemide on blood pressure during late‐onset pre‐eclampsia in patients with high cardiac output2. Issue 1 (3rd November 2016) - Tamás, Péter; Hantosi, Eszter; Farkas, Bálint; Ifi, Zsolt; Betlehem, József; Bódis, József
Abstract: Objective: To examine the effect of furosemide on hypertension and edema in patients with pre‐eclampsia experiencing high cardiac output. Methods: The present cohort study enrolled patients with pre‐eclampsia who were admitted to the pregnancy pathology unit of the Department of Obstetrics and Gynecology, University of Pécs, Hungary, between January 1 and December 31, 2015. Eligible patients had singleton pregnancies with no fetal anomalies, high blood volume, visible edema, and a hematocrit concentration below 37 L/L. Blood pressure was measured and impedance cardiography was used to determine cardiac output for all patients before they received a 40‐mg dose of furosemide; after 60 minutes blood pressure and cardiac output were measured again. Results: The study enrolled 14 patients. Lower cardiac output ( P =0.002), systolic blood pressure ( P =0.002), and diastolic blood pressure ( P =0.002) were recorded after furosemide administration, with patient heart rates remaining stable. Conclusion: The heart‐rate stability suggests that the change of cardiac output was due to a decrease in blood volume. These data suggest that diuretics could be useful in the management of late‐onset pre‐eclampsia, indicating that an increase in water retention could play a role in the development of late‐onset pre‐eclampsia. Abstract : Using diuretics to lower blood volume resulted in decreased blood pressure in patients with pre‐eclampsia who had high cardiac output.